Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557170
|View full text |Cite
|
Sign up to set email alerts
|

Conductor

Abstract: The proliferation of inexpensive connected devices has created a situation where a person, at any given moment, is surrounded by interactive computers. Despite this fact, there are very few means by which a user may take advantage of this large number of screens. We present Conductor, a prototype framework which serves as an exemplar for the construction of cross-device applications. We present a series of interaction methods by which users can easily share information, chain tasks across devices, and manage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(34 citation statements)
references
References 31 publications
1
30
0
1
Order By: Relevance
“…A sizable part of HCI research on cross-device interaction is driven by the vision of enabling users to conduct complex knowledge work (e.g., active reading [9,10], brainstorming [30], sensemaking [16]) by seamlessly working across multiple mobile devices. In this vision, multiple tablets or phones form seamless and powerful device "communities" [39] or "symphonies" [16] that can enhance or even replace traditional desktop devices or large screens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sizable part of HCI research on cross-device interaction is driven by the vision of enabling users to conduct complex knowledge work (e.g., active reading [9,10], brainstorming [30], sensemaking [16]) by seamlessly working across multiple mobile devices. In this vision, multiple tablets or phones form seamless and powerful device "communities" [39] or "symphonies" [16] that can enhance or even replace traditional desktop devices or large screens.…”
Section: Introductionmentioning
confidence: 99%
“…In this vision, multiple tablets or phones form seamless and powerful device "communities" [39] or "symphonies" [16] that can enhance or even replace traditional desktop devices or large screens. This echoes Weiser's vision of ubiquitous computing where mobile "pad" devices (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hamilton and Wigdor [13] implemented Conductor, a cross-device framework that supports interaction methods that allow for managing several activities across multiple devices in an individual desk environment. Hereby, the focus lied on cross-device settings that allow for easy transition of information as well as for managing relationships between devices in an unobtrusive way.…”
Section: From Paper To Interactive Devicesmentioning
confidence: 99%
“…We decided for six tools to trade-off between providing enough functions to engage in multiple activities and to prevent overwhelming. Previous research has shown that individuals can use up to seven tools [4] and are able to benefit from up to ten tablets in cross-device settings [13].…”
Section: Systemmentioning
confidence: 99%
See 1 more Smart Citation